Species diversity of jewel beetles (Coleoptera, Buprestidae) in floodplain habitats of the rivers of South-East Kazakhstan (Experimental biology, 2015)
The major rivers of the desert south-eastern Kazakhstan are the Ile, Karatal, Aksu, Lepsy, Kaskelen, Sharyn, Sheleketc. 45 species of jewel beetles (Coleoptera, Buprestidae) of the 16 genera, belonging to 5 subfamilies: Julodinae (1genus, 1 species, 2.2%), Polycestinae (2 genera, 6 species, 13.3%), Chrysochroinae (4 genera and 14 species, 31.1%),Buprestinae (4 genera, 8 species, 17.8 %), Agrilinae (5 genera, 16 species, 35.6%) are exposed in the floodplain habitatsof desert rivers of South-East Kazakhstan. Sphenoptera (11 species), Agrilus (9 species), Acmaeoderella (5 species)genera are most richly represented. 56% species (28 species) of the fauna of jewel beetles in the floodplain habitats arerare. It include some species occasionally founds in riparian habitats, but are common in arid and semiarid habitats.
Keywords: insects; beetles; borers; fauna; habitat; riparian forests; species; Kazakhstan